Tiny Regulators of Massive Tissue: MicroRNAs in Skeletal Muscle Development, Myopathies, and Cancer Cachexia - Singh, Gurinder Bir; Cowan, Douglas B; Wang, Da-Zhi (Frontiers in Oncology, 2020)
Skeletal muscles are the largest tissues in our body and the physiological function of muscle is essential to every aspect of human life. Regulation of its development, homeostasis, and metabolism is critical for the proper functioning of skeletal muscle. Consequently, understanding the processes involved in the regulation of myogenesis is of great interest. Non-coding RNAs especially microRNAs (miRNAs) are important regulators of gene expression and function. miRNAs are small (about 22 nucleotide) noncoding RNAs known to negatively regulate target gene expression post transcriptionally. miRNAs are abundantly expressed in skeletal muscle. Gain- and loss-of function studies have revealed important roles of this class of small molecules in muscle biology and disease. In this review, we summarize the latest research achievements exploring the role of miRNAs in skeletal muscle development, gene expression, and function as well as in muscle disorders like sarcopenia and Duchenne muscular dystrophy (DMD). Continuing with the theme of the current review series we will also briefly discuss the role of miRNAs in cancer cachexia.